Shared Care Models in the Treatment of Pediatric Attention-Deficit/Hyperactivity Disorder (ADHD) - Meshal A. Sultan; Carlos S. Pastrana; Kathleen A. Pajer (SAGE Publishing, 2018)
Objectives: The aim of this review is to evaluate the effectiveness of shared/collaborative care between mental health-care providers and primary care providers (PCPs) on the outcomes of children and adolescents with attention-deficit/hyperactivity disorder (ADHD). This evaluation will be very helpful in the allocation of ADHD resources for models with the strongest evidence. Methods: Using the Preferred Reporting Items for Systematic Review and Meta-analysis statement, we searched for randomized controlled trials, cohort, case-control, and cross-sectional studies on shared/collaborative care models in the treatment of ADHD. Using MEDLINE, PsycINFO, and CENTRAL databases from January 2000 to December 2016, we retrieved English language articles for review. The validation search identified 75 records. Five studies met the inclusion criteria and were analyzed in this systematic review. There were insufficient data for a meta-analysis. The included studies involved 655 children and adolescents who had a diagnosis of ADHD. The Cochrane Collaboration's tool for assessing risk of bias was used to estimate bias. Results: Overall, the results show that the effects of shared/collaborative care models were small to moderate (effect size: 0.1-0.6, P = .04) on symptom rating scales, but all positively affected functional outcomes (effect size: 0.3-0.7, P = .04-.01). The data indicated that the models were associated with increased PCPs' comfort levels, but the evidence for increased capacity for diagnosing and managing ADHD was weaker. Conclusions: This review concludes that the current studies do not show strong evidence for the outcome of collaboration between PCPs and mental health professionals on ADHD management. Future research should consider providing education to PCPs on management guidelines prior to conducting the trials, and more innovation is needed to discover methods of collaboration that affect the direct care of ADHD.